Knowledge engineering and the semantic web : 5th International Conference, KESW 2014, Kazan, Russia, September 29-October 1, 2014. Proceedings - Mouromtsev, Dmitry; Klinov, Pavel (Communications in Computer and Information Science, 2014)
This book constitutes the refereed proceedings of the 5th Conference on Knowledge Engineering and the Semantic Web, KESW 2014, held in Kazan, Russia, in September/October 2014. The 18 revised full papers presented together with 4 short system descriptions were carefully reviewed and selected from 44 submissions. The papers address research issues related to semantic web, linked data, ontologies, natural language processing, knowledge representation.